Chemical prospecting of Malaysian dipterocarpaceae from UiTM Pahang Forest Reserve (HSUiTM Pahang) / Wan Zuraida Wan Mohd Zain, Shaari Daud and Jamaludin Kasim - Wan Mohd Zain, Wan Zuraida; Daud, Shaari; Kasim, Jamaludin (2008)
A great majority of the Malaysian population relies on indigenous medicinal plants for treatment of diseases. The search for the plant constituents with potential activities for medicinal purposes can be performed successfully by chemical methods and, in combination with biological evaluation. However, the pre-selection process of plants to be investigated is also one of the most important pre-requisites. In the UiTM Pahang Forest Reserve (HSUiTM), there are many plants that have not been evaluated for their potential medicinal value. This paper presents a brief review on resveratrol in dipterocarpaceae plants and their health benefits.